Crystal structure and dynamics of a lipid-induced potential desensitized-state of a pentameric ligand-gated channel - Basak, Sandip (eLife, 2017)
Desensitization in pentameric ligand-gated ion channels plays an important role in regulating neuronal excitability. Here, we show that docosahexaenoic acid (DHA), a key ω−3 polyunsaturated fatty acid in synaptic membranes, enhances the agonist-induced transition to the desensitized state in the prokaryotic channel GLIC. We determined a 3.25 Å crystal structure of the GLIC-DHA complex in a potentially desensitized conformation. The DHA molecule is bound at the channel-periphery near the M4 helix and exerts a long-range allosteric effect on the pore across domain-interfaces. In this previously unobserved conformation, the extracellular-half of the pore-lining M2 is splayed open, reminiscent of the open conformation, while the intracellular-half is constricted, leading to a loss of both water and permeant ions. These findings, in combination with spin-labeling/EPR spectroscopic measurements in reconstituted-membranes, provide novel mechanistic details of desensitization in pentameric channels. DOI: http://dx.doi.org/10.7554/eLife.23886.001